The Impact Of Moving The State Capital To East Kalimantan For The Autonomous Status Of DKI Jakarta - Nurwidya Kusma Wardhani; Wicipto Setiadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to examine the status of DKI Jakarta after the plan to move the National Capital to East Kalimantan. We know that before the plan to move the National Capital, the center of Indonesia, both in terms of government, economy and resources, was centered in the DKI Jakarta area. Of course, after the construction of the National Capital in East Kalimantan, precisely in the North Penajam Paser area, the center of economic government and resources will gradually be moved to the Kalimantan region. This is where the position of DKI Jakarta, which was previously the National Capital, will change status to become a province in general and will give rise to several domino effects that will follow when DKI Jakarta's status no longer becomes the National Capital of Indonesia. The data collection method was carried out by studying literacy and statutory regulations and conducting qualitative descriptive data analysis to find out what the future status of regional autonomy will be for the DKI Jakarta region after the move of the National Capital.